2021
DOI: 10.1007/s00799-021-00312-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-lingual citations in English papers: a large-scale analysis of prevalence, usage, and impact

Abstract: Citation information in scholarly data is an important source of insight into the reception of publications and the scholarly discourse. Outcomes of citation analyses and the applicability of citation-based machine learning approaches heavily depend on the completeness of such data. One particular shortcoming of scholarly data nowadays is that non-English publications are often not included in data sets, or that language metadata is not available. Because of this, citations between publications of differing la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…May (1997) also found serious English language bias in the Institute for Scientific Information (ISI) database, as most non-English journals are not covered by the Science Citation Index (SCI). Cross-lingual citations make up less than two percent of all citations (Saier et al, 2021). In the field of recommender systems, Torres et al (2004) observed that a recommender in a user's native language was greatly preferred to one in an alternative language, even if the items themselves recommended were in the alternative language (e.g., a Portuguese-based recommender recommending scientific papers in English).…”
Section: Unfairness Definitionmentioning
confidence: 99%
“…May (1997) also found serious English language bias in the Institute for Scientific Information (ISI) database, as most non-English journals are not covered by the Science Citation Index (SCI). Cross-lingual citations make up less than two percent of all citations (Saier et al, 2021). In the field of recommender systems, Torres et al (2004) observed that a recommender in a user's native language was greatly preferred to one in an alternative language, even if the items themselves recommended were in the alternative language (e.g., a Portuguese-based recommender recommending scientific papers in English).…”
Section: Unfairness Definitionmentioning
confidence: 99%